Karan guar 14: A new high-yielding and quality gum content variety - JAIN, S K; SHEKHAWAT, S S; GUPTA, K C (The Indian Journal of Agricultural Sciences, 2023)
Guar is a valuable industrial crop, widely grown in India and Pakistan. The industrial potentialities of guar seed are based on a complex polysaccharide called galactomannan (gum) which is present in its endosperm. The newly developed variety Karan Guar-14 has good galactomannan (gum) content (30.2%) and high viscosity profile (3412 cp) which increases its export values. It is medium maturing (90–95 days) and on an average, it gives a higher grain yield (1222 kg/ha) with the superiority of 14.31% over the best check RGC 1033 (1069 kg/ha). This variety also gives higher fodder yield (2567 kg/ha) with a superiority of 18–45% over the check RGC 1066 (1773 kg/ha), RGC 1033 (2110 kg/ha) and HG 2-20 (2180 kg/ha). Seeds are medium bold (2.7–3.3 g/100 grain). It also showed resistance/tolerance to important diseases and insects and was recommended for different states of India, including Rajasthan, Haryana, Gujarat and Maharashtra.